An Exploration of Students' Understanding of Mathematical Concepts Based on the Information Processing System at MAN 1 Muaro Jambi - Oktarino, Randy; Marzal, Jefri; Rohati, Rohati (FKIP - Universitas Riau, 2025)
Understanding mathematical concepts is one of the essential and fundamental aspects of mathematics learning in schools, with the aim of enabling students to develop the ability to understand mathematical concepts, explain the relationships between concepts, and apply concepts or algorithms flexibly, accurately, efficiently, and appropriately in problem-solving. This study aims to analyze and understand the extent to which students comprehend mathematical concepts, as well as to evaluate the effectiveness of the information processing system at MAN 1 Muaro Jambi in supporting students’ understanding of mathematical concepts. This research is exploratory in nature and employs a descriptive qualitative approach. The research subjects consist of three tenth-grade students selected using purposive sampling. The instruments used in this study are a mathematical concept comprehension test on the topic of SPLTV and interviews. Data analysis was conducted by reducing data from written tests and interviews, and by using methodological and source triangulation. The results of the study show that the three subjects demonstrated different levels of conceptual understanding, which were based on the memory storage components involved in each subject. It is therefore concluded that students whose information processing reached the Long Term Memory stage demonstrated a better exploration of mathematical concept understanding compared to those whose processing only reached the Short Term Memory and Sensory Register stages.